Climbing activity in frogs and the effect of highly diluted succussed thyroxine - Endler, P.C.; Pongratz, W.; Kastberger, G.; Wiegant, F.A.C.; Haidvogel, M. (British Homeopathic Journal, 1991)
The experiments investigate the influence of extremely dilute thyroxine (T4) in special ‘homœopathic’ preparation (dilution T4.30x) on the spontaneous tendency of juvenile frogs to leave the water and climb on land. Climbing activity was suppressed by dilution T4.30x, with statistical significance both in comparison to the effect of the ‘potentized’ preparation of the solvent (dilution H2O.30x) as well as in comparison to the control observations before the start of the treatment. Finally, in the search for optimal treatment duration, it was shown that exposure to the dilutions for even a few minutes sufficed to cause significant effects.
Keywords: Homœopathic effect; Diluted hormone; Thyroxine; Amphibia; Activity; High dilution